2002
DOI: 10.1037/0021-843x.111.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion and attributions in the carers of patients with Alzheimer's disease: The effect on carer burden.

Abstract: Burden of care, expressed emotion (EE), causal attributions, and salivary cortisol were assessed in 100 carers of patients with Alzheimer's disease. Forty-one carers were rated high EE, which was associated with higher scores of carer distress and strain, and greater reports of noncognitive features in the patient, but not with cortisol levels. High EE carers made more attributions personal to, and controllable by, the patient for negative events. Critical carers made more attributions of the patient's behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
96
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 48 publications
(77 reference statements)
7
96
1
1
Order By: Relevance
“…In Western countries, EE has been well accepted to be a generalized risk factor associated with caregiver stress in different mental health problems such as schizophrenia, depression and dementia [44]. For example, Tarrier et al [45] found high EE was associated with higher scores of caregiver distress and strain. In the Asian context, a Japanese study using the Camberwell Family Interview Schedule (CFI) [46] found that there was a tendency for lower expression of both positive and negative emotional reactions towards the family member with dementia [47].…”
Section: Coping With the Task Of Caregivingmentioning
confidence: 99%
“…In Western countries, EE has been well accepted to be a generalized risk factor associated with caregiver stress in different mental health problems such as schizophrenia, depression and dementia [44]. For example, Tarrier et al [45] found high EE was associated with higher scores of caregiver distress and strain. In the Asian context, a Japanese study using the Camberwell Family Interview Schedule (CFI) [46] found that there was a tendency for lower expression of both positive and negative emotional reactions towards the family member with dementia [47].…”
Section: Coping With the Task Of Caregivingmentioning
confidence: 99%
“…It is difficult to say that they match exactly with the NAS's criticism and hostility; however, it is certain that the NAS captures aspects that are close to EE. There have been studies targeting families of dementia patients that investigated the relationship between EE and care burden and abuse 18,19,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, la literatura muestra que altos niveles de EE pueden provocar problemas del estado de ánimo en los cuidadores y se relaciona con una peor salud mental y mayor tensión en el cuidador (Scazufca y Kuipers, 1996;Terrier et al, 2002;Wagner, Logsdon y Pearson, 1997;Wearden, Tarrier, Barrowclouch, Zastowny y Rahill, 2000). En el caso de los TCA, los cuidadores con alta EE, a menudo tienen sentimientos de culpa con respecto a la enfermedad (Besharat, Eisler y Dare, 2001).…”
Section: Introductionunclassified